Moonshine: How a Return to the Sunshine policy under President Moon Jae-In will bring Stability to the Korean Peninsula - Malevich, Simon H (Glendon Journal of International Studies, 2020)
Abstract: Following ten years of conservative rule in South Korea, the election of President Moon Jae-In presents an opportunity to improve its relationship with North Korea. A major architect of the Sunshine Policy, many of Moon’s proposed policy changes echo those of the Sunshine Policy. This paper will present and evaluate the merits of the Sunshine Policy, and compare them to Vision 3000: Denuclearization and Openness, the alternative presented during the governments of Lee Myung-bak and Park Geun-hye. Finally, this paper will present the merits of a return to such policies of reconciliation and openness with North Korea, examining the structural factors leading to North Korean proliferation. Résumé : Après dix années de régime conservateur en Corée du Sud, l’élection du président Moon Jae-In est l’occasion d’améliorer ses relations avec la Corée du Nord. Grand architecte de la politique Sunshine, bon nombre de changements proposés par Moon font écho à ceux de la politique Sunshine. Ce document présentera et évaluera les mérites de la politique Sunshine, et les comparera à Vision 3000 : Dénucléarisation et Ouverture, l’alternative présentée pendant les gouvernements de Lee Myung-bak et Park Geun-hye. Enfin, ce document présentera les mérites d’un retour à de telles politiques de réconciliation et d’ouverture avec la Corée du Nord, en examinant les facteurs structurels conduisant à la prolifération nord-coréenne.